Association Between Ferritin Levels and Sepsis in Patients with COVID-19 at Dr. M. Djamil Hospital - Asrini, Diana Nur; Khairsyaf, Oea; Afriani, Afriani (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2024)
Background: Ferritin is an important mediator of immunomodulatory dysregulation and pro-inflammatory effects, which contribute to cytokine storms that could lead to sepsis in a critically ill patients with COVID-19. The role of ferritin as a biomarker of sepsis in those patients is yet fully understood. The aim of this study is to investigate an association between ferritin levels and sepsis in patients with COVID-19.Method: This study was a retrospective, cross-sectional study of 474 COVID-19 hospitalized patients at Dr. M. Djamil Hospital, Padang.Result: Most of the COVID-19 patients in this study were between the ages of 18 and 49 (38,61%), female (55.91%), with moderate clinical illness (40.50%), and had one comorbidity (41,14%) with obesity as the most common comorbidity (37.97%). More than half of patients (54,22%) had ferritin levels of ≥500 ng/mL (median 1,201 ng/mL with a range of 503–12,010 ng/mL). The incidence of sepsis was significantly higher in the group whose ferritin level was ≥ 500 ng/ml compared to those with less ferritin level (P<0.001; OR=3.33; 5.99% vs 17.91%; CI 95%=1.74-6.36).Conclusion: There is a statistically significant association between the ferritin level and sepsis in patiens with COVID-19 at DR M Djamil Hospital.